PKM Pemberdayaan Kelompok Nelayan di Desa Galesong Kota Kabupaten Takalar sebagai Upaya Peningkatan Ekonomi dan Keselamatan Kerja - Alwi, Muhammad Rusydi; Shintarahayu, Balqis; Clausthaldi, Fadhil Rizki; Fajar, Muhammad; Alfira, Alfira (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Galesong Kota is one of the villages in Galesong District, Takalar Regency. Residents in Galesong Kota Village mostly work as fishermen, every day looking for fish across the sea for their survival. The community implements a capture fisheries system. One of the traditional capture fisheries businesses in Galesong Kota Village is called "Karya Bersama". Fishermen partners in Galesong village earn income from fishing which is still relatively low. The value of the fish caught is sometimes not enough to cover the operational costs and daily living expenses of the family. One of the reasons for the lack of fish catches is that fishing boat engines often suffer damage which causes fishermen to be unable to go out to sea. In addition, the knowledge and skills of partner fishermen regarding boat engine repair and maintenance techniques are still very minimal. In this service the methods used are interviews, socialization, and training held in the village of Galesong Kota. The interview method was carried out to find the main problems, followed by socialization and training methods to increase the knowledge and skills of fishermen to maintain boat engines with the Carbon Cleaner technique. The community's understanding and skills in solving problems increase or increase after the service process. And it is hoped that in the future fishing communities can implement their skills in maintaining and repairing machines independently so as to avoid losses caused by damage to the machine.